Associated factors and gender differences of falls in older adults with hypertension: a national cross-sectional survey - Yazhu Wang; Yingying Zhang; Shiwei Cao; Xiyu Chen; Xiaobing Xian; Xiaobing Xian; Tengfei Niu (Frontiers in Public Health)
BackgroundFalls have become a crucial public health problem among older adults, especially those with hypertension. However, the current understanding of the risk of falls among them is still insufficient. The purpose of this study was to investigate the factors associated with falls and their gender differences among older adults with hypertension in China.MethodsBased on the cross-sectional data of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) 2018 database, this study defined 24 possible associated factors based on the five dimensions of the Health Ecology Model. Binary Logistic Regression Model was used to analyze the impact of each factor on falls among older adults with hypertension.ResultsThe prevalence rate of falls in older adults with hypertension in China was 22.60%. Falls are associated with a variety of factors. Specifically, gender, self-rated health, hearing impairment, stroke, instrumental activities of daily living (IADL) disability, basic activities of daily living (BADL) disability, exercise, fresh fruit and taste preference are significant associated factors for falls among older adults with hypertension. Among them, the effects of self-rated health, stroke and exercise on falls are only significant in female with hypertension. The effect of fresh fruit on falls was significant only in men with hypertension.ConclusionThe findings highlight that the current situation of falls among older adults with hypertension requires attention, necessitating comprehensive measures for prevention and control.